KERAGAMAN JENIS DAN PERILAKU PEMANGSA PREDATOR YANG BERASOSIASI DENGAN HAMA KEPIK PENGISAP BUAH KAKAOHelopeltis spp. PADA TANAMAN KAKAO - Yustina Maria Silvia Wonga Puu (AGRICA, 2017)
Helopeltis spp. is one of the pests that attack cocoa fruit and can lead to decreased quality and quantity of fruit. Efforts to control that can be done is the utilization of natural enemy one of them is a predator. The large predator populations in the cocoa ecosystem will decrease the pest population of Helopeltisspp. the aim of this study was to know the predator species of pests associated with Helopeltisspp pests and predatory behavior. This research was conducted in Ende Sub-district in 6 villages and Laboratory of Agricultural Faculty of Flores University from March to May 2017. The method used was observation in the field by taking predator samples and observed their morphology and testing of predatory behavior. The variables observed were predators and behavioral diversity and predator predation time. The results obtained 3 species of predators namely Oecophyllasmaragdina, Gasteracanthacancriformis, and Leucaugevenusta. The diversity of predator types associated with Helopeltis spp. all of which are low in Randorama village of 0.29; Randotonda village 0.31; village Ndetundora I 0.26; village Ndetundora II 0.16; village Ndetundora III 0.18; and Embutheru village 0.23. Predator behavior of each predator differs from the predation time of Oecophyllasmaragdina 47 min/ tail, Gasteracanthacancriformis 1 hour 51 min/tail and Leucaugevenusta 1 hour 29 min/ head.